Valoração econômica dos atrativos turísticos de Guaramiranga-CE - Silva, Gilliard Santos da (2019)
Brazilian tourism has shown a strong upward trend in recent years and, in Ceará, this activity has established itself as one of the main economic forces of the state. In this sense, the Maciço de Baturité and in particular the city of Guaramiranga has drawn attention for its great tourist potential, both in relation to the climate and natural beauty, as well as its architectural heritage, which makes the region recognized as an alternative to the so-called sun and beach tourism. In this context, the objective of this study is to estimate the economic value of tourism in Guaramiranga-CE. To achieve that, the study used the Hybrid Travel Cost Method to estimate the economic value of the city and the Contingent Valuation Method to assess the willingness to pay for Pico Alto, the second highest point in the State of Ceará and third in the Northeast Region. The study has a quantitative nature and a field research was carried out, with the application of 521 questionnaires with visitors from the city of Guaramiranga-CE and the data were analyzed in Microsoft Excel® and statistically in SPSS®. The average tourist profile of Guaramiranga is 32 years old, lives in Fortaleza-CE, has a monthly family income of R$ 7 thousand, has a complete college education and goes to Guaramiranga by car. It was found that aspects related to the tranquility of nature and the pleasant climate are the elements that most motivate tourists to go to Guaramiranga-CE. The multiple linear regression was significant for the following variables: travel cost, income, age, distance to Guaramiranga and staying in the city. According to the econometric model presented, these variables help to explain the frequency of visits to Guaramiranga. The average willingness to pay for the tourist use of Pico Alto was R$ 50.94 per person, with the annual value of R$ 27 million. On the other hand, when considering all the variables analyzed by the Travel Cost Method, the economic impact of tourism in Maciço de Baturité reaches more than R$ 185 million per year. This study can serve as a reference for decision-making related to tourism, both by the local management of Guaramiranga and the state government of Ceará.